The Powers in PowerPoint: Embedded Authorities, Documentary Tastes, and Institutional (Second) Orders in Corporate Korea. Issue 2 (19th March 2019) - Prentice, Michael M.
ABSTRACT: Microsoft PowerPoint is both the bane and banality of contemporary South Korean office work. Corporate workers spend countless hours refining and crafting plans, proposals, and reports in PowerPoint that often lead to conflicts with coworkers and overtime work. This article theorizes the excessive attention to documents in modern office contexts. Where scholars have been under the impression that institutional documents align with institutional purposes, I describe a context in which making documents for individual purposes and making them for work exist under a basic tension. Based on fieldwork in corporate Korea between 2013 and 2015, I describe how Korean office workers calibrate documents to the tastes of superiors who populate the managerial chain. These practices leave little trace of real "work" on paper, but they are productive for navigating complex internal labor markets and demonstrating a higher order value of attention toward others. These findings suggest that institutional and individual authorities are not competing projects inside organizations but become entangled in increasingly complex participatory encounters, even as they are channeled through a seemingly simple software like PowerPoint. [ documents, expertise, authority, technology, South Korea ] RESUMEN: Microsoft PowerPoint es tanto la perdición como la banalidad del trabajo de oficina surcoreano contemporáneo. Los trabajadores corporativos gastan incontables horas refinando y elaborando planes, propuestas, y reportes en PowerPoint que a menudo llevan a conflictos con sus compañeros de trabajo y a horas extras de trabajo. Este artículo teoriza la excesiva atención a documentos en los contextos de oficina modernos. Donde los investigadores han estado bajo la impresión que los documentos institucionales se alinean con propósitos institucionales, describo un contexto en el cual crear documentos con propósitos individuales y crearlos por trabajo existen bajo una tensión básica. Basado en trabajo de campo en la Corea corporativa entre 2013 y 2015, describo cómo trabajadores de oficina coreanos calibran documentos a los gustos de los superiores que pueblan la cadena directiva. Estas prácticas dejan poco rastro de "trabajo" real sobre el papel, pero son productivas para navegar los mercados de labor internos complejos y demostrar un valor de más alto orden de atención hacia otros. Estos hallazgos sugieren que autoridades institucionales e individuales no son proyectos competitivos dentro de las organizaciones, pero se llegan a enredar en encuentros participativos cada vez más complejos, aun cuando se canalizan a través de un software aparentemente simple como PowerPoint. [ documentos, experiencia, autoridad, tecnología, Sur Corea ]